Perjanjian Tidak Dipoligami dalam Pernikahan Menurut Mazhab Syafii dan Hukum Positif di Indonesia - Afrianto, Fikri; Fahmi, Muhammad Nurul (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2023)
The purpose of this research is to discuss the marriage agreement, especially the agreement not to be polygamous according to Mazhab Syafii and positive law in Indonesia. Marriage is a way for humans to channel their biological desires from a path that is in accordance with Islamic law. In marriage itself, Allah also regulates the law of polygamy, namely that a man may marry a wife with a maximum limit of 4 people. However, in reality, not all women or wives want to be polygamous, so they take precautions to make a marriage agreement before carrying out the contract so as not to be polygamous. The research method used is qualitative research. The type of research used is the literature review method, so that the data sources used are sourced from relevant documents. The results of this study are a marriage agreement in the form of a prospective wife not wanting to be polygamized by a prospective husband, when the marriage has taken place, the scholars in the Syafii Mazhab consider the agreement invalid even though the marriage is valid with the consequence of canceling the mahr that has been determined before the contract and the wife only gets mahr mitsl, while in positive law in Indonesia the agreement is permissible, as long as the agreement is agreed upon by both parties, both the male party (prospective husband) and the female party (prospective wife) and does not harm third parties. However, if after the marriage the agreement is violated, then the wife has the right to file a marriage annulment or make it a reason for a divorce suit to the Religious Court.